2012
DOI: 10.1159/000339693
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Chronic Hepatitis C and a Pancreatic Mass in Endoscopic Ultrasound

Abstract: We report a rare case of pancreas tumor (lymphoma) in a patient with a history of chronic hepatitis C virus (HCV) infection without treatment, with a high viral load (20,199,805 IU/ml). He presented with abdominal pain, jaundice, weight loss and sweating. Computed tomography showed a hypodense mass located in the head of the pancreas, and immunohistochemistry of a specimen obtained by endoscopic ultrasound-guided fine needle aspiration revealed non-Hodgkin’s lymphoma of the pancreas, B cell type. An associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Takagi et al 5 and Ghobakhlou et al 1 also showed cases of patients with CHC who developed a pancreatic malignancy. One study by Huang et al showed that with 340 819 person-years in the HCV cohort, 34 pancreatic cancers were identified.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Takagi et al 5 and Ghobakhlou et al 1 also showed cases of patients with CHC who developed a pancreatic malignancy. One study by Huang et al showed that with 340 819 person-years in the HCV cohort, 34 pancreatic cancers were identified.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic HCV infection has been associated with many extrahepatic manifestations including the development of B-cell non-Hodgkin's lymphoma (NHL). Primary pancreatic lymphoma is very rare and comprises 2.2% of NHL and 4.9% of all pancreatic malignancies 1. We report a patient with early stage HCV infection who developed and died of complications from a primary pancreatic lymphoma.…”
Section: Introductionmentioning
confidence: 95%
“…With the exception of the male predominance, these trends were consistent with the characteristics of the present case. On the other hand, anti-HCV antibody was detected in our patient and she was considered to be in a post-infection state of hepatitis C. There are several reports of patients with malignant lymphoma and a history of HCV infection (5,6), and the tropism of the lymphoid tissue, which occurs in HCV, has been suggested to be responsible for several immune-mediated disorders such as mixed cryoglobulinemia (7). At the present time, however, there is no accepted evidence to show that HCV induces the carcinogenesis of B-cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly associated with immunosuppression, related to HIV infection or solid organ transplantation ( 139 ). A few studies have implied that HCV or HBV infection is associated with PPL ( 140 , 141 ).…”
Section: Primary Pancreatic Lymphomamentioning
confidence: 99%